1976
DOI: 10.1177/105256297600200103
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Simulation: Treating the Classroom as an Organization

Abstract: No matter what style of teaching is used, the classroom is an organization. An in other organizations, goals must be set, decisions made, work allocated, and members recruited, motivated, controlled and rewarded.Whether or not the instructor chooses to make explicit the parallels between other organizations and the classroom, issues such as leadership, structure and control still must be handled and how they are handled will have great impact. Students probably learn as much from our classroom managerial behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…Like others who argue for treating the classroom as an organization (Cohen, 1976), we stress that the class should serve as a learning laboratory in which students and faculty alike can practice improving leadership skills. We are aware of the challenges of this approach and have also found that students sometimes experience it as disorienting (see Mezoff, Cohen, & Bradford, 1979).…”
Section: Role Modelingmentioning
confidence: 98%
“…Like others who argue for treating the classroom as an organization (Cohen, 1976), we stress that the class should serve as a learning laboratory in which students and faculty alike can practice improving leadership skills. We are aware of the challenges of this approach and have also found that students sometimes experience it as disorienting (see Mezoff, Cohen, & Bradford, 1979).…”
Section: Role Modelingmentioning
confidence: 98%
“…Essentially, CAO creates a functioning organization; every student is an active participant with responsibilities that reach across the organization and the professor becomes the senior manager. As described by Cohen (1976), the objective of the CAO: …is not to simulate an organization, but rather to create genuine organizational issues for students, to put them in the position of an organizational member who must deal with such problems as: how does work get allocated; how does one work with others who bring different expertise to tasks; how does one influence and motivate subordinates, peers and superiors; how does one cope with ambiguity in solving difficult tasks which do not have any obviously correct single answer; how can disagreements among coworkers be resolved; and how will decisions be made. (p. 14) While proponents of CAO indicate they would never go back to a teacher-centered classroom, our recent experience in the CAO community suggests it has not become widely adopted since its initial description by Cohen (1976).…”
Section: The Shadow Side Of Teaching Classroom As Organizationmentioning
confidence: 99%
“…CAO is best described as an heutagogy: "the study of self-determined learning … an attempt to challenge some ideas about teaching and learning that still prevail in teacher centered learning" (Hase & Kenyon, 2000). Different models of CAO vary in the degree to which students are responsible for content delivery, classroom facilitation, and assessment of work (e.g., Balke, 1981;Bright et al, 2016;Cohen 1976;Cotton 1976;Goltz, 1992;Lawrence, 1992; McDonald, Spence & Sheehan 2011; Oddou, 1987;Romme, 2003;Sheehan, McDonald & Spence, 2009). Learning emerges from students engaging in Kolb's (1984) The alluring promise of CAO, it's "persona", is transformative learning (Mezirow, 1994) and student engagement.…”
Section: Classroom As Organizationmentioning
confidence: 99%
“…Other CAO designs arrange students into a formal organizational hierarchy with managers and subordinates. Student managers grade their subordinates, who in turn grade the managers (Cohen, 1976;Gardner & Larson, 1988).…”
Section: Examples Of Meta-practices In Usementioning
confidence: 99%